Sistem Informasi Manajemen Layanan Laporan Pelanggaran Siswa Berbasis Website di SMK XYZ Purbalingga - Eka Tripustikasari; Nanda Pujiono; Fiby Nur Afiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Education is one of the tools used to form a noble personality and discipline. Vocational High School is a school that is very influential on the formation of personal students. But in everyday reality many problems are increasingly complex, for example deviating from school rules, fights between students, cheating during exams. To form a high student discipline personality, a better school role is needed. In the current era of computerization, a system is needed that can facilitate the flow of information on violations of discipline so that the school can handle it quickly. With the existence of a website-based student violation report service application system at Purbalingga YPT 2 Vocational School, students are expected to be able to actively report the violation actions they have encountered, so the school quickly follows up. To describe this system model in the form of a context diagram and Data Flow Diagram (DFD). In implementing this student violation report service system, use php for the programming language and MySQL for the database.